Performance Analysis of 3-Level 5-Phase Multilevel Inverter Topologies - B. Jyothi; M. Venu Gopala Rao (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Now a day’s many industrial applications requires high power. Some other appliances may require intermediate power either more or less depending upon their operation. With these consequences, MULTI LEVEL INVERTERS are introduced in 1975.for above intermediate voltage applications. The name MULTI LEVEL began with the three-level converter.By enormous advancement in power semiconductor switches, in electric drives increasing the phase number greater than the conventional three phase especially in locomotives, naval, aerospace, and electrical vehicles industry has many advantages than three phase. In this view, here five phase VSI has developed. This paper aims at comparing the performance of conventional two level inverter Diode clamped and Capacitor clamped topologies of 5-phase multilevel inverter (3-level) using sinusoidal pulse width modulation. SPWM is highly economical, has more efficiency, controllability. These circuits are analyzed by using simulation software package such as MATLAB.